Tinnitus in Adults, a Health Problem: Implications for the Society and the Scientific Community: Acufeno em Adultos, um Problema de Saúde: Implicações para a Sociedade e para a Comunidade Científica - Haider, Haúla Faruk; Paço, João C.; Hall, Deborah A. (Gazeta Médica, 2018)
Tinnitus is a phantom sound perceived in the absence of external acoustic stimulation, which is only heard by the affected person. It is described in a variety of ways and can be a single sound or combination of different sounds. Tinnitus is related to many other conditions and has an impact in the quality of life of the affected person. However, pathophysiological mechanisms underlying tinnitus and their basic biological remains unknown. One of the major challenges, concerning the heterogeneity of the tinnitus condition, is the lack of standardization in research and clinical management. For this, the TINNET, a European Cost Action for research, has the main objective to develop better strategies for diagnosis and management. The establishment of guidelines for clinical diagnosis, treatment, neuroimaging assessments and outcome assessment, through the identification of clinically meaningful tinnitus subtypes, provides an important basis for the standardization of clinical research and management of tinnitus.